Performance of Polar code in diversity reception system - Pingheng ZHAI; Binsong SHEN; Jinbo LIANG (Dianxin kexue)
Diversity reception is one of the most effective ways to resist fading over Rayleigh fading channels,in order to improve the performance of Polar codes over Rayleigh fading channels,a diversity reception system based on Polar code was proposed.The information bit selectionsequences of Polar codes in diversity reception were determined,and the upper bound of BER for Polar codes in diversity reception system was derived.The simulation results show that when quadruple diversity reception is used,the encoding gain is greater than 3 dB and has 0.6 dB performance advantage compared to LDPC code.Experiment results show that,when eightfold diversity is used,the encoding gain is greater than 5 dB and has 1.5 dB performance advantage compared to LDPC code,and diversity reception can significantly improve the performance of the system.